PENERAPAN E-GOVERNMENT DALAM MENINGKATKAN PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI KECAMATAN LASUSUA (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The application of e-government in the context of realizing good governance was a form of improving the quality of public services, increasing active participation in providing information to the public, and increasing the need to be more effective in providing information. This study aimed to determine the implementation of e-government in BPJS Kesehatan in Lasusua District. This study used a qualitative examination procedure. Data was collected through techniques; interviews, observations and documentation. The results of research regarding the application of e-government in improving BPJS Health services in Lasusua District showed that; (1) the willingness of the BPJS head to implement e-government in providing services (2) for the government to provide the benefits of open, participatory, innovative and accountable governance. The benefit for the community  made it easier to obtain health services. (3) resources, including human resources and financial resources to support the sustainability of e-government implementation.